Pyrobaculum aerophilum sp. nov., a novel nitrate-reducing hyperthermophilic archaeum. - Völkl, P (1993)
A novel rod-shaped hyperthermophilic archaeum has been isolated from a boiling marine water hole at Maronti Beach, Ischia, Italy. It grew optimally at 100 degrees C and pH 7.0 by aerobic respiration as well as by dissimilatory nitrate reduction, forming dinitrogen as a final product. Organic and inorganic compounds served as substrates during aerobic and anaerobic respiration. Growth was inhibited by elemental sulfur. The cell wall was composed of a surface layer of hexameric protein complexes arranged on a p6 lattice. The core lipids consisted mainly of glycerol diphytanyl glycerol tetraethers with various degrees of cyclization. The G+C content was 52 mol%. The new isolate resembled members of the genera Thermoproteus and Pyrobaculum by its ability to form characteristic terminal spherical bodies ("golf clubs"). On the basis of its 16S rRNA sequence, the new isolate exhibited a close relationship to the genus Pyrobaculum. It is described as a new species, which we name Pyrobaculum aerophilum (type strain: IM2; DSM 7523).